Relevance of Laser Flare Photometry in Retinal Pathologies - Schöneberger, Verena; Menghesha, Leonie; Feltgen, Nicolas; Fuchsluger, Thomas Armin; Cursiefen, Claus; Schaub, Friederike (Klinische Monatsblätter für Augenheilkunde, 2023)
Laser flare photometry provides a non-invasive and objective measurement of the Tyndall effect in the anterior chamber. The laser flare value (measured in photon number per millisecond [pc/ms]) thus quantifies the extent of disruption to the blood-aqueous barrier and can be used in clinical applications to monitor uveitis therapy or to measure the postoperative degree of inflammation. Standardised performance must be observed during measurement. Publications of the last 35 years on laser flare photometry deal not only with the measurement procedure but also with its use in clinical practice for different ophthalmological pathologies. Likewise, various influencing factors have already been investigated and described that must be considered when measuring and evaluating laser flare values. The focus of this article is the relevance of laser flare photometry in retinal pathologies. In recently published studies, the level of objective tyndallometry in primary rhegmatogenous retinal detachment is shown to depend on lens status, symptom duration, and extent of retinal detachment. The greater is the area of the retina affected, the greater the disruption of the blood-aqueous barrier appears to be. Elevated laser flare values have also been considered as a predictor for the development of proliferative vitreoretinopathy (PVR). However, based on current knowledge, this assumption must be put into perspective. According to current data, objective tyndallometry can be used to monitor the progression of intraocular inflammation and to quantify the blood-aqueous barrier, and the values correlate with the extent and anatomical features, as well as the symptom duration in retinal detachment. Many influencing factors have already been identified. But further evaluation is desirable and needed. It is still unclear whether laser flare values can be used in the future as a predictor for sequelae such as PVR development.
Keywords: laser flare photometry; Tyndall effect; inflammation; proliferative vitreoretinopathy; retinal detachment